Gastrointestinal Symptoms in Systemic Sclerosis: Prevalence and Severity across Disease Subtypes and Autoantibody Profiles - Vujović Šestakov, Marina; Lukovic, Sretko; Pavlovic, Ivana; Zlatanovic, Maja; Ostojic, Predrag (Acta medica Lituanica, 2026)
Background: This study aimed to evaluate the prevalence and severity of gastrointestinal (GI) symptoms in patients with systemic sclerosis (SSc), their impact on social functioning and emotional well-being, and to compare findings between patients with limited cutaneous systemic sclerosis (lcSSc) and diffuse cutaneous systemic sclerosis (dcSSc), as well as between patients positive for anticentromere (ACA) or anti-topoisomerase I (ATA) antibodies.Materials and methods: Forty-two consecutive patients with SSc were included: 31 with lcSSc and 11 with dcSSc. ACA antibodies were detected in 26 patients, and ATA antibodies in 16 patients. The UCLA SCTC GIT 2.0 self-assessment questionnaire was used to assess the severity of GI symptoms across seven subscales: reflux, distention/bloating, diarrhea, fecal soilage, constipation, social functioning, and emotional well-being.Results: Symptoms of reflux (lcSSc/dcSSc = 64.5%/81.8%), distention/bloating (lcSSc/dcSSc = 61.3%/81.8%), constipation (lcSSc/dcSSc = 45.2%/45.5%), and fecal soilage (lcSSc/dcSSc = 6.4%/18.2%) were similarly frequent in lcSSc and dcSSc. Diarrhea was more common in dcSSc (45.5% vs. 16.1%, p = 0.04), with a higher median index value (0.25 vs. 0.00, p = 0.02), thus indicating more severe symptoms. No differences were observed in the prevalence or severity of GI symptoms between ACA- and ATA-positive patients. Median index values for social functioning and emotional well-being did not differ by the disease subtype or antibody status.Conclusions: Diarrhea was more prevalent and more severe in patients with dcSSc, while other gastrointestinal manifestations showed no major differences between subtypes. Symptom prevalence and severity did not differ according to the antibody status, and their impact on social and emotional functioning was similar across the groups.
Keywords: systemic sclerosis; gastrointestinal symptoms; patient-reported outcomes; UCLA SCTC GIT 2.0